Mrs Una West and Mrs June Southwell interviewed by Bert Sheedy in the Bert Sheedy and Marj Sheedy oral history collection - West, Una.; Southwell, Jane.; Sheedy, P. B. (Philip Bert) (1974)
Folkloric recording.
A collection of interviews collected by Bert and Marj Sheedy concerning the history of the Canberra district and its people.
Also available online
Keywords: West, Una -- Interviews; Southwell, Jane -- Interviews; Canberra Region (A.C.T.) -- History